Pension plan characteristics and framing effects in employee savings behavior - David Edward Card; Michael R. Ransom (Institute for the Study of Labor (IZA), 2007)
In this paper we document the importance of framing effects in the retirement savings decisions of college professors. Pensions in many post-secondary institutions are funded by a combination of an employer contribution and a mandatory employee contribution. Employees can also make tax-deferred contributions to a supplemental savings account. A standard lifecycle savings model predicts a dollar-for-dollar tradeoff between supplemental savings and the combined regular pension contributions made on behalf of an employee. Contrary to this prediction, we estimate that each additional dollar of employee contributions leads to a 70 cent reduction in supplemental savings, whereas each dollar of employer contributions generates only a 30 cent reduction. The asymmetry which is consistent with different mental accounts for employer and employee contributions provides further evidence of the sensitivity of individual savings decisions to the precise details of their pension plan.
Keywords: 330; Alterssicherung; Sozialversicherungsbeitrag; Private Rentenversicherung; Verhaltensökonomik; Sparen; USA